(untitled) (Research, Society and Development, 2024)
Background: Temporomandibular disorder (TMD) is a set of conditions with a multifactor etiology that affect the temporomandibular joint and muscles of mastication. Objective: The aim of the present study was to assess the effectiveness of treatment for myofascial TMD using acupuncture and low-level laser therapy compared to occlusal splint. Methods: 23 patients recruited through announcements and online publications. The diagnosis of TMD was confirmed using the Research Diagnostic Criteria for TDM (RDC/TMD) and all participants had moderate to severe pain upon palpation. The participants were randomly allocated to three groups: Group 1–occlusal splint; Group 2–10 sessions of acupuncture (once per week); Group 3–low-level laser therapy at 48-h intervals until the remission of symptoms or until completing 10 sessions. The participants were submitted to evaluations before and after treatment as well as 30 days after the end of treatment involving the determination of pain intensity, maximum vertical mandibular movement, as well as extraoral and intraoral palpations e analyze intra e extra group. Results: Statistically significant improvements in pain intensity were found in the acupuncture and laser groups (p=0.002). Improvements in the masseter and temporal muscles as well as the lateral pole of the temporomandibular joint were achieved with acupuncture and laser. Significant improvement was found in the posterior mandibular region using all three treatment modalities. Improvement in the submandibular region was only achieved with laser therapy. Conclusion: Treatments with acupuncture and low-level laser were more effective at reducing symptoms in individuals with myofascial TMD compared occlusal splint.